Strategic planning in the implementation of an e-government regional system: The Porto Santo case - Daniel Polónia (2014)
This article describes the process of designing a strategy for e-government, which is under implementation in the Autonomous Region of Madeira. It describes the initial strategic vision, based upon the implementation of a small scale pilot in the island of Porto Santo. In light of this vision, the article makes an analysis of state of the art with regard to e-government initiatives in islands and interoperability problems in e-government initiatives at European level. Given the state of the art, we present a generic conceptual model that promotes the reuse of existent information, concepts, standards, solutions and specifications. This model is based on modular components and loosely coupled services, and the implementation of this concept is embodied by a Service Oriented Architecture. Based on this model a roadmap for implementation is defined, including three levels of maturity of the services to be integrated: "as is" mediated; and automatic.